Pandangan Masyarakat terhadap Walimatul ‘Urs Janda Bakirai di Kenagarian Koto Sani Kecamatan X Koto Singkarak Kabupaten Solok - Jumelda Zalimah; Sofia Ridha (Lembaga Yasin AlSys, 2026)
Differences in the implementation of walimatul ‘urs for janda bakirai and unmarried women in Kenagarian Koto Sani have generated diverse community views, particularly regarding restrictions on the form of the wedding celebration and the imposition of a customary sanction in the form of a fine of two emas for violators. This study aimed to analyze the implementation of walimatul ‘urs for janda bakirai and community views regarding these customary provisions. The study employed a qualitative approach with a descriptive field research design. Primary data were obtained through interviews with customary leaders, members of the Kerapatan Adat Nagari, community leaders, and janda bakirai, whereas secondary data were derived from books, journals, and supporting documents. Data were collected through observation and interviews and were subsequently analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the implementation of walimatul ‘urs for janda bakirai differed from that for unmarried women, as they were only permitted to hold a simple ceremony, were not allowed to wear a suntiang or organize artistic performances, and were subject to a fine of two emas for violating the customary provisions. Community views were divided into two groups: those who supported the provisions because they were considered a marker of marital status and a means of preserving customary traditions, and those who rejected them because the sanctions were considered burdensome and less relevant to current societal conditions. This study confirms that the customary provisions regarding walimatul ‘urs for janda bakirai continue to be observed despite generating differing views within the community. These findings contribute to the development of customary law studies and provide practical implications for customary authorities in evaluating the existing provisions so that cultural values can be preserved without disregarding the principles of social justice.